Differentiation between 3,4- and 4,15-Epoxyeudesmanolides by Electrospray Ionization Tandem Mass Spectrometry - Herbert Júnior Dias; Ricardo Stefani; José Carlos Tomaz; Ricardo Vessecchi; Antônio Eduardo Miller Crotti (Journal of Analytical Methods in Chemistry)
We investigated the fragmentation of the eudesmanolide-type sesquiterpene lactones 1α-(4-hydroxymethacryloyloxy)-3α,4α-epoxy-8α-hydroxyeudesm-11(13)-6α,12-olide (1) and 1α-(2,3-epoxyangeloyloxy)-4α,15-epoxy-8α-hydroxyeudesm-11(13)-6α,12-olide (2) by electrospray ionization tandem mass spectrometry (ESI-MS/MS). The elimination of the different ester substituent at C(1) directly from protonated 1 and 2 (A) led to the formation of two regioisomer product ions B (A − RCO2H). Further fragmentation of B resulted from consecutive eliminations of H2O and CO molecules. However, we identified four product ions that allowed for the differentiation between 3,4- and 4,15-epoxyeudesmanolides. The formation of these diagnostic ions was associated with the C(3)–O bond of compound 1, which propitiates the participation of the lone pair of the oxygen epoxide in the formation of B through a Grob-Wharton-type fragmentation, then resulting in an alternative fragmentation pathway. These data can be useful for the fast differentiation between epoxyeudesmanolide regioisomers directly from Dimerostemma extracts by liquid chromatography-tandem mass spectrometry (LC-MS/MS), as an alternative to NMR, or even for quantitation studies of these compounds using multiple reaction monitoring (MRM) scan.